Two channel data acquisition system for heart sound segmentation algorithm based on instantaneous energy of electrocardiogram - Malarvili, M. B.; J., M. Najeb; Ismail, Kamarulafizam (2003)
This paper presents the hardware design of 2- channel data acquisition system for heart sound and Electrocardiogram (ECG) to capture the heart sound and ECG simultaneously from patients; and software algorithm to detect the first heart sound (S1) and second heart sound(S2). The algorithm utilizes Instantaneous Energy of ECG to estimate the presence of S1 and S2. Thus, heart sound segmentation can be done as it is essential in the automatic diagnosis of heart sounds. The Instantaneous Energy of ECG is performed to verify the occurrence of S1 and S2 as it is widely accepted pathologically that Phonocardiogram (PCG) and Electrocardiogram (ECG) are two noninvasive source of information depicting the cardiac activity [6]. The hardware consists of instrumentation amplifier, filter, isolation amplifier for each channel, multiplexer, Analogue to Digital Converter (ADC) and microcontroller 68HC11 to control and handle communication protocols with PC. The algorithm was tested for 210 cardiac cycles of heart sound and ECG recorded from patients from normal and abnormal simultaneously.